DETERMINATION OF MOISTURE CONTENT IN FOOD PRODUCTS (European Journal of Emerging Technology and Discoveries, 2024)
In this article, determining the moisture content in food products when evaluating product quality, the moisture content of products is an important indicator that affects safety, durability and other technological aspects. In practice, various methods are used to study meat and meat products using specialized equipment such as drying cabinets. Sample preparation (release from the shell, grinding to the desired size, mixing) is one of the important stages of testing. For examination, the samples are placed in a glass container with a crushed stopper. In food enterprises, as a rule, the mass fraction of moisture in the raw material of the product is controlled regardless of the form of its binding, i.e. humidity is determined. Humidity is expressed as a percentage. When determining humidity, the thermogravimetric method and the refractometric method are most often used.